Child Preparedness Model in Facing Landslide Disasters - Ika Rahmawati; Putri Kristyaningsih (Journal of Ners and Midwifery, 2023)
Vulnerability in children occurs due to limited understanding of the risks that occur around them, resulting in a lack of preparedness. The Child Preparedness Model is a disaster management effort that focuses on children's preparedness in facing disasters. This research was carried out in stages, namely analyzing children's preparedness in facing landslides, followed by developing a Child Preparedness model to increase children's preparedness in facing landslides. The design of this research was a  quantitative with a cross sectional approach. The research population was 120 children in Blimbing Village, Kediri Regency. The sampling technique used purposive sampling. The research instrument used a questionnaire to determine children's readiness to face the risk of landslides. The independent variable of this research was the Child Preparedness model and the dependent variable was children's readiness to face landslides. The data analysis by the SEMPLS test showed that input influences process control (p=0.001), process control influences effectors (p=0.01), effectors influence output (p=0.02), output influences resilience (p=0.004). There is a need to increase children's role in disaster management so that they are better prepared to face landslides.